Infração contratual do tipo falta grave : uma análise a partir da contratação de serviço terceirizado por meio do pregão eletrônico - Chiarelli, Márcia May (Universidade do Vale do Rio dos Sinos, 2019)
The study was conducted in the light of Institutional Theory, which assumes that the purpose of institutions is to establish a structure of human interaction capable of reducing uncertainty in relationships in a given society. In other words, the Institutions are configured as formal and informal rules, which structure human interactions and establish the possibilities of functionality and economic outcome of organizations. This research I 've to focus the formal rules, which refer to aspects of legal and procedural related to procedures adopted in public procurement. These rules structure the outsourcing of outsourced service contracts made by the public administration. Hiring that reflects in social benefit, regarding the generation of employment and income to the workers, especially the low income ones, reducing the size of the payroll and promoting economy to the state, based on the perspective of public governance. With the publication of Decree 9.507 / 2018, the possibility of outsourcing by the phas been expanded, as the new decree only points to cases in which outsourcing is prohibited. In this context, the present study aimed to evaluate whether the savings obtained on an electronic trading floor impact on the likelihood of serious misconduct occurring during the execution of the contract. Serious misconduct is a type of contractual breach that occurs when the company does not fulfill the labor obligations agreed in the contract. A logistic regression was used to analyze whether there is a likelihood of relating the savings obtained in electronic trading with the occurrence of a serious lack of contractual execution of the outsourced services outsourcing. However, the hypothesis did not present statistical significance. However, other factors pointed out in the literature were significant as explanations of the occurrence of severe absence. This study allows society to know the dynamics surrounding outsourcing services through the use of electronic trading, in addition to the widely publicized benefits such as economy, transparency and speed. In addition, it provides insights into the discussion of the existing dichotomy between its benefits and its harms, the latter often unknown or undisclosed, such as: the high rate of contractual breach, especially the serious misconduct type, the constant occurrences of contract termination and also the short duration of the contracts.
Keywords: Terceirização; Serviço Continuado; Pregão Eletrônico; Infração Contratual; Teoria Institucional; Outsourcing; Continued Service; Electronic trading floor; Contractual Infringement; Institutional theory; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis